Oral fluid testing can be used to monitor xenotransplant donor herds for porcine cytomegalovirus/roseolovirus status - Schommer, Susan K.; Samuel, Melissa S.; Whitworth, Kristin M.; Byrne, Addison K.; Wells, Kevin D.; Prather, Randall S. (Frontiers in Veterinary Science, 2024)
A major concern of xenotransplantation is that donor organs may be a source of pathogens. One pathogen in particular, porcine cytomegalovirus (PCMV), a porcine roseolovirus (PRV), is thought to result in donor organ failure in an immunosuppressed state. Porcine cytomegalovirus is difficult to detect in organ donor swine because of its ability to establish latency. Establishment of an antemortem testing protocol to monitor and maintain PCMV/PRV negative herd status decreases the risk of inadvertently using an organ harboring the virus. Oral fluid has become a common sample for detecting a number of porcine pathogens. A real-time PCR assay was adapted to include an internal control for inhibition and results from antemortem samples (blood, oral fluid) were compared to postmortem spleen from pigs in a known positive herd. When using both oral fluid and blood to test pigs over 12 months of age 13/20 animals with positive spleens tested real-time PCR positive. Animals younger than 12 months of age were tested individually and in group housing with all pigs positive by oral fluid and/or blood. PCMV/PRV testing of oral fluid in young animals and a combination of blood and oral fluid in older animals can be used to verify that a herd has been kept PCMV/PRV free, as in the high biosecurity facility of the National Swine Resource and Research Center.